Structural Features of the Nucleosomal DNA Modulate the Functional Binding of a Transcription Factor and Productive Transcription - Vinayachandran, Vinesh; Bhargava, Purnima (Frontiers in Genetics, 2022)
A small non-histone protein of budding yeast, Nhp6 has been reported to specifically influence the transcription of a yeast gene, SNR6. The gene is essential, transcribed by the enzyme RNA polymerase III, and codes for the U6snRNA required for mRNA splicing. A translationally positioned nucleosome on the gene body enables the assembly factor TFIIIC binding by juxtaposing its otherwise widely separated binding sites, boxes A and B. We found histone depletion results in the loss of U6 snRNA production. Changing the rotational phase of the boxes and the linear distance between them with deletions in 5 bp steps displayed a helical periodicity in transcription, which gradually reduced with incremental deletions up to 40 bp but increased on further deletions enclosing the pseudoA boxes. Nhp6 influences the transcription in a dose-dependent manner, which is modulated by its previously reported co-operator, an upstream stretch of seven T residues centered between the TATA box and transcription start site. Nhp6 occupancy on the gene in vivo goes up at least 2-fold under the repression conditions. Nhp6 absence, T7 disruption, or shorter A–B box distance all cause the downstream initiation of transcription. The right +1 site is selected with the correct placement of TFIIIC before the transcription initiation factor TFIIIB. Thus, the T7 sequence and Nhp6 help the assembly and placement of the transcription complex at the right position. Apart from the chromatin remodelers, the relative rotational orientation of the promoter elements in nucleosomal DNA, and Nhp6 regulate the transcription of the SNR6 gene with precision.